Developing Youtube Content Using Podcast to Improve Students Speaking Skill - Soffanuddien, Entol Arie; -, Fitri Hilmiyati; -, Afif Suaidi (VISION, 2023)
This research was designed to develop learning media products to improve students' abilities at Madrasah Aliyah Mathlaul Anwar Pusat Menes, Pandeglang, Banten. This was done based on research questions 1) how to design a product using a podcast through the ADDIE Model stage (analysis, design, development, implementation, evaluation) on improving the speaking skills of class XI IPA 2 students of Madrasah Aliyah Mathlaul Anwar Pusat Menes through the use of podcasts? 2) how is the effectiveness of the product on improving the speaking ability of students of class XI IPA 2 Madrasah Aliyah Math'laul Anwar Pusat Menes through the use of podcasts and the research. the research objectives are 1) to design teaching media products through the ADDIE Model stage (analysis, design, development, implementation, evaluation ) using podcasts 2) to find out the results of product effectiveness on students' speaking abilities using podcasts. This study uses a development research design and data collected from 22 students in one class (control class). The results of this study are shown from the pre-test and post-test value data, the results of the data obtained from the use of the T-Paired Table on the aspect of assessing speaking ability. Then for the result of the research found that have significance for students.